2014
DOI: 10.1002/jrs.4552
|View full text |Cite
|
Sign up to set email alerts
|

Raman analysis of proteoglycans simultaneously in bone and cartilage

Abstract: Bone and cartilage are connective tissues with distinct organic matrix (collagen and non‐collagenous proteins) composition facilitating their biological function. Proteoglycans (PGs), a member of the non‐collagenous proteins fulfill functions that are determined by both their core protein and their glycosaminoglycan chains. The purpose of the present study was to identify Raman bands that are representative of PG concentration and may be used in both bone and cartilage tissues. To achieve this goal, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 67 publications
(157 reference statements)
8
74
1
Order By: Relevance
“…With that in mind, we found that the bands near ∼1410 cm –1 (ν s (COO – ) of GAG provided a better contrast than the commonly used (ν s (S=O) peak near 1061 cm –1 . 23 This univariate analysis of the Raman spectroscopy data allows a localization of the main components of articular cartilage, namely, collagen, GAG, water, chondrocytes, and their nuclei.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With that in mind, we found that the bands near ∼1410 cm –1 (ν s (COO – ) of GAG provided a better contrast than the commonly used (ν s (S=O) peak near 1061 cm –1 . 23 This univariate analysis of the Raman spectroscopy data allows a localization of the main components of articular cartilage, namely, collagen, GAG, water, chondrocytes, and their nuclei.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The residual spectral variance of 10.75% was mainly associated with the chondrocyte spectral signature (i.e., cytoplasmic biomolecules and DNA) and other minor ECM biomolecules. 23 Of note, we took into account the anisotropic Raman scattering in the biochemical analysis of collagen by using the total collagen content, which was calculated as the sum of collagen fibers aligned perpendicular and parallel to the tissue surface (see Figure S3). …”
Section: Results and Discussionmentioning
confidence: 99%
“…Another pertinent peak was observed at ca. 1061 cm −1 in the MCL and MDL PCs, which is known to be a key spectral marker for proteoglycans (41,42). This finding offers an intriguing insight into the nature of molecular modifications in the pre-metastatic niche, particularly in light of the study of Gao et al .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the CH 3 symmetric deformation peak at 1,375 cm ¡1 may be a better choice for glycosaminoglycans if calcified cartilage is included in the analyses (68).…”
Section: ¡1mentioning
confidence: 99%